Point Processing Method for Improving Dental Radiology Image Quality - Retno Supriyanti; Ariep Soelaiman Setiadi; Yogi Ramadhani; Haris Budi Widodo (Institute of Advanced Engineering and Science, 2016)
Radiology field is very important in today's world, especially in the field of medicine including dentistry. Radiology equipment that is popular in dentistry is the panoramic machine. A panoramic image facilitate the dentist in making a diagnosis of the abnormality in the mouth and teeth. But unfortunately, for developing countries like Indonesia, panoramic machine available are low resolution which have an effect on the resulting image also has low quality. This research aims to improve the quality of the panoramic image to have a better quality. We use point processing method with emphasis on contrast stretching method. We chose this method because it is quite simple but has a high performance. Based on the second opinion from the hospital, the performance is 83.9%, therefore this method is promising to be implemented on the improvement of dental radiology images.